2018
DOI: 10.1007/s11011-018-0191-9
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal MR imaging in hepatic encephalopathy: state of the art

Abstract: Hepatic encephalopathy (HE) is a neurological or neuropsychological complication due to liver failure or portosystemic shunting. The clinical manifestation is highly variable, which can exhibit mild cognitive or motor impairment initially, or gradually progress to a coma, even death, without treatment. Neuroimaging plays a critical role in uncovering the neural mechanism of HE. In particular, multimodality MR imaging is able to assess both structural and functional derangements of the brain with HE in focal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 101 publications
0
13
0
Order By: Relevance
“…DTI, which has been used in some research studies, could be performed in this setting in the near future because these sequences are now commonly available and provide important information about pathophysiology (Fig. ) . In addition, DTI is used to more precisely determine the longterm prognosis after acute brain injuries, such as in cases of cardiac arrest or traumatic brain injury …”
Section: How To Assess Neurological or Neurocognitive Complications Omentioning
confidence: 99%
See 1 more Smart Citation
“…DTI, which has been used in some research studies, could be performed in this setting in the near future because these sequences are now commonly available and provide important information about pathophysiology (Fig. ) . In addition, DTI is used to more precisely determine the longterm prognosis after acute brain injuries, such as in cases of cardiac arrest or traumatic brain injury …”
Section: How To Assess Neurological or Neurocognitive Complications Omentioning
confidence: 99%
“…This particular indication for LT, which is based on persistent HE that is being adequately treated, has been, until now, based solely on an expert’s evaluation and not on any additional and specific complementary exploration. Some of these patients may have been wrongly diagnosed with HE, which could explain an incomplete recovery after LT. How useful would a multimodal MRI be in this setting? Answering this question would open a door that could provide access to LT only to patients with a major chance of improvement and would restrict access to patients with previously undiagnosed cerebral alterations who have a high probability of decompensation after LT.…”
Section: Future Directionsmentioning
confidence: 99%
“…ScanRT investigates the rescue from working memory (ventral‐medial area), that is, the type of memory we use to remember a phone number between reading it and typing it. All such functions are known to be affected by HE, and a reduction in gray matter volume in the implicated anatomical areas has been documented in patients with cirrhosis and HE …”
Section: Discussionmentioning
confidence: 99%
“…All such functions are known to be affected by HE, 41 and a reduction in gray matter volume in the implicated anatomical areas has been documented in patients with cirrhosis and HE. 42 All the computerized tests (sRT, cRT and ScanRT) were performed after a short practice run because unpublished data relating to a previous study from our group 43 had shown that 80 normal controls improved significantly when these tests were repeated. It should however be highlighted that this is a result dating back to 1999, a time when the use of the computers was not as widespread as it is now, especially in people in their 40s-60s.…”
Section: Discussionmentioning
confidence: 99%
“…So far, brain imaging has provided useful insight into the pathophysiology of HE [20]. Details are also provided in the paper by Butterworth [21] on the pathogenesis of HE in cirrhosis in this Supplement.…”
Section: Imagingmentioning
confidence: 99%